Development and validation of an iPad-based Japanese language monosyllable speech perception test (iCI2004 monosyllable). (1st March 2021) - Nishio, Shin-ya; Tono, Tetsuya; Iwaki, Takako; Moteki, Hideaki; Suzuki, Kumiko; Tsushima, Yui; Kashio, Akinori; Akamatsu, Yusuke; Sato, Hiroaki; Yaegashi, Keiko; Takeda, Hidehiko; Kumagai, Fumiai; et al.
Abstract: Background: Speech perception tests are commonly used as indices reflecting hearing ability in daily life. In Japan, the CI-2004 test, first developed in 2004, is widely used as standard, but it was not validated against a large number of normal hearing controls and hearing loss patients. Aims/objectives: The primary objective of the present study was to develop and validate iPad-based software for the Japanese monosyllable speech perception test, 'iCI2004'. Material and methods: Seven universities and two medical centers participated in this study. The hearing threshold and Japanese monosyllable speech perception test results of 77 people with normal hearing and 459 people with hearing loss were collected. Results: All participants with normal hearing achieved almost perfect perception results both in quiet and in noise. For cochlear implant users, the average monosyllable speech perception score was 55.1 ± 19.6% in quiet and 40.3 ± 19.2% in noise (SNR + 10dB). Conclusions and significance: We developed iPad-based Japanese monosyllable speech perception test software and validated it by testing a large number of controls and hearing loss patients with cochlear implants or hearing aids. The developed monosyllable speech perception test has a sufficiently large dynamic range for assessing improvement in speech perception in Japanese cochlear implant users.